Advanced control strategies for the multicolumn countercurrent solvent gradient purification process. Issue 7 (6th March 2016) - Papathanasiou, Maria M.; Avraamidou, Styliani; Oberdieck, Richard; Mantalaris, Athanasios; Steinebach, Fabian; Morbidelli, Massimo; Mueller‐Spaeth, Thomas; Pistikopoulos, Efstratios N.
Abstract : The multicolumn countercurrent solvent gradient purification process (MCSGP) is a semicontinuous, chromatographic separation process used in the production of monoclonal antibodies) . The process is characterized by high model complexity and periodicity that challenge the development of control strategies, necessary for feasible and efficient operation and essential toward continuous production. A novel approach for the development of control policies for the MCSGP process, which enables efficient continuous process control is presented. Based on a high fidelity model, the recently presented PAROC framework and software platform that allows seamless design and in‐silico validation of advanced controllers for complex systems are followed. The controller presented in this work is successfully tested against disturbances and is shown to efficiently capture the process periodic nature. © 2016 American Institute of Chemical Engineers AIChE J, 62: 2341–2357, 2016